New trends associated with disease activity in patients with ulcerative colitis: New trends in ulcerative colitis - Buran , Tahir; Kılınç, Sanem Gökçe Merve; Sahin , Mustafa (Journal of Surgery and Medicine, 2024)
Background/Aim: The severity and extent of ulcerative colitis (UC) guide us in determining the treatment method for each case. It has been suggested in the literature that high neutrophil-lymphocyte and platelet-lymphocyte ratios can serve as markers of active ulcerative colitis. This study retrospectively analyzes the relationship between neutrophil-lymphocyte ratio and platelet-lymphocyte ratio with clinical activity indices and endoscopic activity indices in predicting disease severity in patients with ulcerative colitis. There are few studies in the literature regarding the relationship between platelet-lymphocyte ratio (PLR) and disease activation in ulcerative colitis. This study contributes to the follow-up and outcomes of these patients, as there is a lack of sufficient retrospective studies on the platelet/lymphocyte ratio in patients diagnosed with UC in our country and worldwide. Methods: This study is a population-based, single-center, case-controlled study. It was conducted by retrospectively analyzing the hospital information system for data recorded during the routine diagnosis and treatment of ulcerative colitis patients followed and treated at Celal Bayar University Medical Faculty Gastroenterology Division between January 2014 and December 2021. A total of 135 patients with ulcerative colitis were included in the study. The patients were divided into 2 groups, active disease and disease in remission, based on clinical activity indices and endoscopic activity indices. Erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), hemoglobin (Hb), white blood cell (WBC), neutrophil-lymphocyte ratio (NLR), and platelet-lymphocyte ratio (PLR) levels were checked during routine follow-up of patients with ulcerative colitis. These values were recorded at the first presentation to the hospital and 3 months after treatment. Results: Laboratory values at presentation were compared with those at the third month of treatment in a group of 113 patients with UC in remission: NLR (5.529 (3.485) and 4.374 (2.335), [P<0.001]), erythrocyte sedimentation rate (26.81 (20.42) and 21.78 (19.32), [P=0.015]), C-reactive protein (4.087 (6.729) and 1.696 (3.525), [P<0.001]), and white blood cell count (9,864 (3,514) and 8,067 (1,927), [P<0.001]) were found to be lower than the baseline values. As expected, decreases in inflammatory markers were observed in patients in remission. In a group of 22 patients with active disease, values at presentation were compared with those at the third month of treatment: neutrophil count (8,508 (2,908) and 9,646 (3,265), [P=0.037]) and platelet count (289,591 (95,123) and 323,364 (127,647), [P=0.010]) were found to be high. Similarly, ESR (19.63 (15.43) and 27.89 (21.11), [P=0.036]) was found to be high. These values were higher in active disease compared to the time of admission. Conclusion: In our study, neutrophil-lymphocyte ratios and platelet-lymphocyte ratios were significantly higher in patients with active ulcerative colitis. The level of inflammatory markers in ulcerative colitis patients at the time of diagnosis and in the early stages of the disease is helpful in predicting the course of the disease, and this was shown to be related to clinical, endoscopic, and laboratory indices. These inflammatory markers can predict disease activity alone or in combination. However, a threshold value could not be calculated due to the insufficient number of patients, and thus, more comprehensive prospective studies are needed.